Hop Aroma and Hoppy Beer Flavor: Chemical Backgrounds and Analytical Tools—A Review. (2nd January 2018) - Rettberg, Nils; Biendl, Martin; Garbe, Leif-Alexander
ABSTRACT: Hops are the most complex and costly raw material used in brewing. Their chemical composition depends on genetically controlled factors that essentially distinguish hop varieties and is influenced by environmental factors and post-harvest processing. The volatile fingerprint of hopped beer relates to the quantity and quality of the hop dosage and timing of hop addition, as well as the overall brewing technology applied. Analytically, the aroma of hops and the flavor of hoppy beers cannot be measured by quantification of a single odorant; moreover, the selection of several key compounds or a comprehensive characterization (profiling) seems reasonable. Analysis of hops and beer is challenging. The selective enrichment of volatiles from complex matrices, separation, unambiguous identification, and precise quantification are the keywords used in this context. This review outlines the synthesis of relevant hop aroma compounds within the plant. The process that incorporates hops into the final beer is described using the hopping techniques used in the industry. Due to the complexity and multiplicity of chemical compounds found in hops, an attempt was made to simplify the information presented by separating the chemical compounds considered into two broad groups: terpenoids and nonterpenoids. This review summarizes approaches commonly used for analysis of hop aroma compounds in hops and beer.